Can Physical Exercise Improve the Residents' Health? - Li, Cong; Chen, Jin-Hong; Liu, Xi-Hua; Ren, Shu-Qi (Frontiers in Public Health, 2021)
With the rapid development of China's economy and society, the quality of life of residents has continued to improve, and the concept of health has gradually taken root in the hearts of the people. This paper uses the 2018 data of the China Family Panel Studies (CFPS) to analyze the internal mechanism and influencing factors of participating in physical exercise on the health level of residents. The results show that participating in physical exercise can significantly improve the subjective and objective health level of residents, and the result passed two important robustness tests. Heterogeneous test shows that the degree of influence of participation in physical exercise on the health level of residents varies according to the different regional and individual characteristics; the effect of urban residents' physical exercise to improve their health level is better than that of rural residents; and the effect of physical exercise on the improvement of health level is more obvious in the eastern and western areas, those who have not completed compulsory education, and those with high incomes. This study will have strong guiding significance for the improvement of the overall level of national health in China and will provide a theoretical basis and guiding opinions for the construction of healthy China.